A Note on Inclusion Intervals of Matrix Singular Values - Shu-Yu Cui; Gui-Xian Tian (Journal of Applied Mathematics)
We establish an inclusion relation between two known inclusion intervals of matrix singular values in some special case. In addition, based on the use of positive scale vectors, a known inclusion interval of matrix singular values is also improved.